Population Structure and Recent Evolution of Plasmodium falciparum - Rich, Stephen M.; Ayala, Francisco J. (Proceedings of the National Academy of Sciences - PNAS, 2000)
Plasmodium falciparum is the agent of malignant malaria, one of mankind's most severe maladies. The parasite exhibits antigenic polymorphisms that have been postulated to be ancient. We have proposed that the extant world populations of P. falciparum have derived from one single parasite, a cenancestor, within the last 5,000-50,000 years. This inference derives from the virtual or complete absence of synonymous nucleotide polymorphisms at genes not involved in immune or drug responses. Seeking to conciliate this claim with extensive antigenic polymorphism, we first note that allele substitutions or polymorphisms can arise very rapidly, even in a single generation, in large populations subject to strong natural selection. Second, new alleles can arise not only by single-nucleotide mutations, but also by duplication/deletion of short simple-repeat DNA sequences, a process several orders of magnitude faster than single-nucleotide mutation. We analyze three antigenic genes known to be extremely polymorphic: Csp, Msp-1, and Msp-2. We identify regions consisting of tandem or proximally repetitive short DNA sequences, including some previously unnoticed. We conclude that the antigenic polymorphisms are consistent with the recent origin of the world populations of P. flaciparum inferred from the analysis of nonantigenic genes.